2023
DOI: 10.3389/feart.2023.1161989
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave velocity structure in the middle segment of the Xiaojiang fault zone using ambient noise tomography

Abstract: The middle segment of the Xiaojiang fault zone consists of strike-slip faults with frequent strong and medium–strong earthquakes under the joint influence of NE-trending faults and deep structural characteristics. The distribution characteristics of the deep subfaults of each branch need to be revealed. Two short-period dense array survey lines are deployed in the area. Shear wave velocity structures are obtained using ambient noise tomography. The results reveal that the faults in each branch dip nearly eastw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
1
1
0
Order By: Relevance
“…The authors observed a strong seismic velocity gradient across the fault along the distributed acoustic sensing (DAS) line. Such velocity variations are also observed in the Xiaojiang fault zone (Liang et al, 2023).…”
Section: Introductionsupporting
confidence: 56%
“…The authors observed a strong seismic velocity gradient across the fault along the distributed acoustic sensing (DAS) line. Such velocity variations are also observed in the Xiaojiang fault zone (Liang et al, 2023).…”
Section: Introductionsupporting
confidence: 56%
“…Ambient noise tomography has been widely used to build regional or global shear wave velocity models. Recently, this method has been applied to study the structure beneath cities (Li et al, 2016;Liang et al, 2018Liang et al, , 2019a. The advantages of this method are: (1) it does not rely on earthquake data, so is applicable to regions lacking seismic activity, such as Jinan; (2) compared with active source methods, it is cheaper and easier to implement (Liu et al, 2015); (3) the shear wave velocity revealed by ambient noise tomography is especially sensitive to water, so it is highly suitable for use in studying the water migration in Jinan.…”
Section: Methods and Datamentioning
confidence: 99%